Sustainable agriculture and the environment - Farooq, Muhammad, 1978-; Gogoi, Nirmali; Pisante, Michele, Prof (Academic Press, an imprint of Elsevier, 2023)
Sustainable Agriculture and the Environment describes the relationship of agriculture, society, nature and the environment, sustainable agriculture and sustainable development goals, management of biophysical resources for sustainable food and environment, traditional knowledge and innovative options, and social and policy aspects of sustainable agriculture. The book presents both environmental and economic principles, helping readers in the development and application of robust policy and good institutional systems that execute on sustainable agriculture practices for a healthy environment and to combat climate resilience.